PENGARUH LOVE OF MONEY DAN RELIGIOSITAS TERHADAP PERILAKU ETIS (STUDI PADA KARYAWAN MUSLIM DI SEKTOR PERBANKAN) - Shabrina Dwi Nova; Fanny Martdianty (School of Business, Bogor Agricultural University (SB-IPB), 2021)
This study aimed to examine the conceptual model covering the variable of love-of-money, religiosity, organizational commitment, salary satisfaction, and ethical behavior on the samples of Muslim employees in the banking sector. This study used a quantitative design by collecting data from 637 respondents based on purposive sampling. The data processing was conducted using Structural Equation Modeling (SEM) method, with LISREL 8.8 software. This study found that love-of-money directly and negatively affected ethical behavior, while religiosity had a significant and positive effect on ethical behavior. Unlike the love-of-money variable that only directly and significantly affected ethical behavior, this study proved the indirect effect of religiosity on ethical behavior through salary satisfaction and organizational commitment. Keywords: love of money, religiosity, ethical behavior, pay satisfaction, organizational commitment